2007
DOI: 10.1103/physrevlett.99.067801
|View full text |Cite
|
Sign up to set email alerts
|

Flexoelectric Blue Phases

Abstract: We describe the occurence and properties of liquid crystal phases showing two dimensional splay and bend distortions which are stabilised by flexoelectric interactions. These phases are characterised by regions of locally double splayed order separated by topological defects and are thus highly analogous to the blue phases of cholesteric liquid crystals. We present a mean field analysis based upon the Landau-de Gennes Q-tensor theory and construct a phase diagram for flexoelectric structures using analytic and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 11 publications
2
46
0
Order By: Relevance
“…The gravitational waves responsible for this asymmetry can be measured in the B-mode polarization of the CMB. 3 Further work connecting chiral gravitational waves to observables can be found in [5][6][7][8].…”
Section: A Overview Of the Mechanismmentioning
confidence: 99%
“…The gravitational waves responsible for this asymmetry can be measured in the B-mode polarization of the CMB. 3 Further work connecting chiral gravitational waves to observables can be found in [5][6][7][8].…”
Section: A Overview Of the Mechanismmentioning
confidence: 99%
“…This theory is motivated by anomaly cancelation in curved spacetimes, string theory and particle physics [2]. Its nonminimal coupling might explain flat galaxy rotation curves without introducing dark matter [3] and future gravitational wave detections might be sensitive to such a modification through frame dragging, gyroscopic precession, and amplitude birefringence in propagation of gravitational waves [4][5][6]. Although it has been stablished that GW170817 falsifies some classes of modified gravity theories which dispense with the need of dark matter [7], recently, it has been shown that CSMG is compatible with such experimental data [8].…”
Section: Introductionmentioning
confidence: 99%
“…The difference is that the gravitational Chern-Simons term is, in spite of appearances, actually Lorentz invariant. The profound puzzle that faces us is that it appears to be possible for a Lorentz-violating b µ term in the fermion sector to generate a radiative correction that is proportional to b µ and fully P violating [27,28,29], yet which is invariant under all rotations and Lorentz boosts.…”
Section: The Puzzle Of Gravitational Radiative Correctionsmentioning
confidence: 99%